Tumor Size as a Critical Prognostic Factor in T1-2 Stage Esophageal Cancer - Zilong Wu; Bentong Yu (Gastroenterology Research and Practice)
Background. Tumor size has been measured in esophageal cancer for decades, but the role of tumor size in relation to T stage in the prediction of survival is still underappreciated. Thus, the present study is aimed at investigating the influence of T stage on the predictive value of tumor size in clinical stage I–IV esophageal cancer patients. Materials and Methods. Data were obtained from the Surveillance, Epidemiology, and End Results Program (SEER) cancer registry program. Cox proportional hazards regression was utilized to identify the independent prognostic ability of the factor. Kaplan-Meier analysis was used to estimate the distribution of survival outcome. Harrell’s concordance index (c-index) was used to quantify the predictive ability of the prognostic model and prognostic factor. Results. According to the T stage, subgroup analysis showed that tumor size was not an independent risk factor in T3 and T4 stage esophageal cancer patients. Furthermore, the predictive power of tumor size was negatively impacted by the increase in T stage. Furthermore, the discriminative ability of the Cox model based on the tumor-node-metastasis (TNM) system with tumor size outperformed the model based on the TNM system only. Conclusion. The current study identified tumor size as a critical clinical prognostic signature for esophageal cancer with considerable discriminatory ability and prognostic value. Therefore, tumor size should be included in the American Joint Committee on Cancer (AJCC) TNM staging of T1-2 esophagus cancer patients.